Influence of Service Quality Dimensions On Passengers Satisfaction at Type-A Giwangan Bus Station Yogyakarta - Mursyid, Mursyid; Fahlefi, Wilis; Wahyudiyono, Wahyudiyono; Dwi Maelana, Herman Wahyu (Business Management Journal, 2023)
The purpose of this study was to determine the significant effect of service quality which consists of dimensions of physical evidence, reliability, responsiveness, assurance and attention to passenger satisfaction at type A Giwangan Bus Station Yogyakarta. The data was obtained by distributing a questionnaire to 100 passengers. The data is processed by instrument test, multiple linear regression test and hypothesis testing including t test, F test and R2 test. The data calculation process uses the Statistical Package for the Social Sciences (SPSS) software version 20. The results of the study concluded that service quality consisting of dimensions of tangibles, reliability, responsiveness, assurance and emphaty has a significant partially and simultaneously influence on passenger satisfaction at type A Giwangan Bus Station Yogyakarta.